2018
DOI: 10.21926/obm.transplant.1901041
|View full text |Cite
|
Sign up to set email alerts
|

KAS Turns Four: The State of Deceased Donor Kidney Allocation in the U.S.

Abstract: Background: This study examines very recent trends in deceased donor kidney transplantation to assess the performance of the kidney allocation system (KAS), implemented December 4, 2014, and whether bolus effects associated with KAS have stabilized nearly four years after implementation. Methods: The overall number of deceased donor kidney transplants, as well as the proportion of transplants by recipient and transplant characteristics, were calculated monthly from December 2013 through September 2018 and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Early post-KAS analyses revealed trends regarding transplant rates across CPRA groups, but extrapolating these trends into the future proved challenging given the bolus effects seen immediately post-implementation. Analyses at the first, second, third, and fourth years post-KAS provided clarity regarding the types of patients who had benefited from the changes introduced and indicated that the system had stabilized over time [5,6,[10][11][12][13]. Ostensibly fueled by the overall rise in donors, TRs steadily increased under KAS for all groups with one notable exception, the highly sensitized group (CPRA 99.9%+), whose TR remained less than half that of the average candidate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Early post-KAS analyses revealed trends regarding transplant rates across CPRA groups, but extrapolating these trends into the future proved challenging given the bolus effects seen immediately post-implementation. Analyses at the first, second, third, and fourth years post-KAS provided clarity regarding the types of patients who had benefited from the changes introduced and indicated that the system had stabilized over time [5,6,[10][11][12][13]. Ostensibly fueled by the overall rise in donors, TRs steadily increased under KAS for all groups with one notable exception, the highly sensitized group (CPRA 99.9%+), whose TR remained less than half that of the average candidate.…”
Section: Discussionmentioning
confidence: 98%
“…The changes made by KAS have made remarkable strides in providing equity in access to transplants while also balancing utility. Recently implemented amendments to KAS that replaced the Donor Service Area distribution with 250 nautical mile circles may further increase transplant rates for those who are harder to match with due to biological reasons and those who are predicted to have high re-transplant rates, among other factors [12,13,15,16]. The clarity in acceptable anti-A2 titers may also increase transplantation among the ABO-incompatible recipients.…”
Section: Fundingmentioning
confidence: 99%
“…For those with CPRA values above 99.9%, benefit has been less evident, with the overwhelming majority of candidates either dead, delisted or still waiting after 3 years compared to those transplanted 3 . Despite a short‐lived “bolus” effect after the implementation of the current KAS, patients with a CPRA > 99.9% continue to have transplant rates far below other highly sensitized patients 14‐17 . In this analysis, 13 XM+ imlifidase‐treated patients with CPRA ≥ 99.9% were considered those with the highest unmet medical need, unlikely to be transplanted, and despite these immunologic challenges, demonstrated outcomes comparable to the overall group.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies examining deceased donor kidney discards, we chose to keep our study at the donor level (as opposed to the kidney level) and did not exclude kidneys transplanted to specific groups such as high Calculated Panel Reactive Antibodies or multiorgan candidates or en bloc transplants. Recent evidence suggests that approximately 10% of all kidney transplants occur within the high Calculated Panel Reactive Antibodies population . Limiting the study population to standard allocation policy may overestimate our ability to identify deceased donor kidneys at risk of being placed.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that approximately 10% of all kidney transplants occur within the high Calculated Panel Reactive Antibodies population. 19 Limiting the study population to standard allocation policy may overestimate our ability to identify deceased donor kidneys at risk of being placed. Our rationale for a donor level analysis was that key variables found in previous studies, such as biopsy results and pump parameters, are typically not available at the time of match.…”
Section: Definition Of Cohort and Outcomementioning
confidence: 99%